2013
DOI: 10.2478/s11535-012-0110-8
|View full text |Cite
|
Sign up to set email alerts
|

Zooplankton communities of inter-connected sections of lower River Oder (NW Poland)

Abstract: The aim of this study was the determination and comparative analysis of the zooplankton communities between the inter-connected sections of the lower Oder river in relation to physicochemical factors. The study was performed at five sites of Oder. Two sites were localized in the main channel of Oder (East Oder), other sites were localized in the west arm of Oder and at the beginning of the canal carrying the post-cooling water from the power plant, and the last site was below at the shallow channel joining the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 32 publications
3
16
0
3
Order By: Relevance
“…The explicit dominance of Rotifera (69 % of total number of taxa, Fig. 2) is in accordance with the well-known fact that in large rivers they have a much higher number of taxa and much greater density than Cladocera and Copepoda [28] and that the contribution of rotifers in zooplankton communities often exceeds 70 % [29].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The explicit dominance of Rotifera (69 % of total number of taxa, Fig. 2) is in accordance with the well-known fact that in large rivers they have a much higher number of taxa and much greater density than Cladocera and Copepoda [28] and that the contribution of rotifers in zooplankton communities often exceeds 70 % [29].…”
Section: Discussionsupporting
confidence: 84%
“…This corresponds with the data of Djurkovic et al [18], as well as with the data recorded by Gulyás [4], who researched zooplankton of the Danube and several of its tributaries (Sava included). The dominance of the representatives of these genera was also recorded in other European rivers [29][30][31][32][33]. Table 3 Jaccard's similarity index (C j ) (1-14 sampling points, see Table 1 It is rather interesting that among the planktonic crustaceans no high individual number of species was found.…”
Section: Discussionmentioning
confidence: 78%
“…In autumn, all the groups of zooplanktons prevailed in numbers in different rivers and in different proportions, but the biomass was essentially determined by the members of Cladocera. The major trends in seasonal changes of the community of crustaceans and rotifers observed at the stations of study were common for lotic communities (Czerniawski et al, 2013;Gromova et al, 2013).…”
Section: Discussionmentioning
confidence: 88%
“…The analysis of the data on the community of crustaceans and rotifers in the regulated Oder River revealed that the most important factor that determines the condition of zooplankton and the physic-chemical properties is WRT (Czerniawski et al, 2013). The influence of hydrochemical factors on the zooplankton of the Novosibirsk reservoir is also connected to the peculiarities of hydrological regime in the parts of the water body (Dvurechenskaya and Yermolaeva, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation